RES IN LOW-ENERGY BUILDINGS - Wantuch, Agnieszka (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2016)
In recent years emphasis has been placed on the production of electrical energy from renewable energy sources (RES) because they seem ecologically safe and inexhaustible. This article presents a basic analysis of the economic viability of the replacement plant for the production of energy-powered conventional sources for RES. The example is a single-family residential building. Analysis performed for the photovoltaic installation.